Ferris, Emil. My Favorite Thing Is Monsters, Fantagraphics, 2017, 416 pages. Sousanis, Nick. Unflattening, Harvard UP, 2015, 208 pages. - Wilma Romatz (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
Ferris, Emil. My Favorite Thing Is Monsters, Fantagraphics, 2017, 416 pages. Sousanis, Nick. Unflattening, Harvard UP, 2015, 208 pages.
Keywords: Emil Ferris; Nick Sousanis